THE PLACE OF JOURNALISTIC STYLE IN THE LANGUAGE SYSTEM (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article scientifically examines the role of journalistic style in the language system, its functional features in speech, and its application in mass media. The communicative functions of journalistic style, factors of expressiveness, and the possibilities of using lexical and stylistic units are analyzed. In addition, the article discusses the problems and future prospects of observing speech culture norms in modern mass media.